2022
DOI: 10.3390/ma15020542
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Fracture Behavior of Cementitious Composites Reinforced with Aligned Hooked-End Steel Fibers

Abstract: Aligning steel fibers is an effective way to improve the mechanical properties of steel fiber cementitious composites (SFRC). In this study, the magnetic field method was used to prepare the aligned hooked-end steel fiber cementitious composites (ASFRC) and the fracture behavior was investigated. In order to achieve the alignment of steel fibers, the key parameters including the rheology of the mixture and magnetic induction of electromagnetic field were theoretically analyzed. The results showed that, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…• Wall dimensions: the larger the wall, the further the fiber must travel, and therefore the more likely it will rotate. This has consequences, from a structural standpoint, on the post-cracking behavior of fiber-reinforced concrete slabs [70]. In any case, the results presented in Fig.…”
Section: Content and Orientation Of Fibersmentioning
confidence: 90%
“…• Wall dimensions: the larger the wall, the further the fiber must travel, and therefore the more likely it will rotate. This has consequences, from a structural standpoint, on the post-cracking behavior of fiber-reinforced concrete slabs [70]. In any case, the results presented in Fig.…”
Section: Content and Orientation Of Fibersmentioning
confidence: 90%
“…It was found that hook-ended steel fibers resulted in better improvement in the tensile performance compared with straight steel fibers. Khan et al [ 30 ] found that aligning the steel fibers in the desired direction using magnetic field while the concrete is still in a fresh state resulted in the significant enhancement of the cracking and ultimate loads of concrete. Abed et al [ 31 ] reported improvement in the flexure and shear performance of self-compacting concrete incorporating steel and polypropylene fibers with increasing dosage of the fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their significant environmental benefits, the use of RCAs in the concrete industry is still limited to nonstructural applications due to their inferior properties compared with those of NAs [2][3][4]. The addition of steel fibers to cement-based mixtures improves the tensile strength, postcracking tensile resistance, flexural strength, and energy absorption capacity [5,6]. Steel fibers have a potential to transform the mode of failure of cement-based mixtures from quasi-brittle to pseudo-ductile through bridging micro-and macro-cracks caused by an applied load [6].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of steel fibers to cement-based mixtures improves the tensile strength, postcracking tensile resistance, flexural strength, and energy absorption capacity [5,6]. Steel fibers have a potential to transform the mode of failure of cement-based mixtures from quasi-brittle to pseudo-ductile through bridging micro-and macro-cracks caused by an applied load [6]. As such, one of the solutions proposed in the literature to improve various properties of concrete with RCAs is the addition of steel fibers [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%